2015
DOI: 10.4149/neo_2015_084
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-141 regulates the tumour suppressor DLC1 in colorectal cancer

Abstract: Our previous study has showed that DLC1 acts as a functional tumor suppressor in colorectal cancer (CRC) cell lines. The aims of this study were to determine whether DLC1 is a target of MicroRNA (miRNA) regulation and to evaluate the role of this mechanism in CRC. By bioinformatics approach and literature, miR-141 was chosen for further study. The miR-141 mimic, miR-141 inhibitor were synthesized and transfected to Lovo cells. Cell growth was determined by MTT and in vivo models. The flow cytometric analysis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…e The samples from early relapse patients showed significantly decreased miR-494 expression levels (P = 0.016). f The samples from early relapsed patients showed significantly decreased let-7b expression levels (P = 0.002) Yang et al J Transl Med (2016) 14:108 that miR-141 has oncogenic characteristics in CRC and prostate cancer [42,43]. Yin et al identified miR-141 as a potential circulating biomarker for metastasis [44], consistent with our findings of high miR-141 expression in early relapsed CRC patients.…”
Section: Discussionsupporting
confidence: 87%
“…e The samples from early relapse patients showed significantly decreased miR-494 expression levels (P = 0.016). f The samples from early relapsed patients showed significantly decreased let-7b expression levels (P = 0.002) Yang et al J Transl Med (2016) 14:108 that miR-141 has oncogenic characteristics in CRC and prostate cancer [42,43]. Yin et al identified miR-141 as a potential circulating biomarker for metastasis [44], consistent with our findings of high miR-141 expression in early relapsed CRC patients.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, some potential genes have been previously reported that they are the direct targets of miR-141 and are associated with cell proliferation and metastasis of human cancers. For examples, PAPP-A, a factor of metabolic process, is frequently found in invasive breast cancer [26, 27]; FUS, a binding protein, is associated with neuroblastoma’s proliferation, migration and survival [28]; DLC1 is a well-known tumor suppressor for a variety of human cancers [29]; as well as IRS2 is a suppressor of cell proliferation and invasion of thyroid cancer [30]. Interestingly, there is a potential target, SIK1, has previously reported to be associated with anoikis resistance and metastasis via interaction with LKB1 and in p53-dependent manner [31].…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, some of the possible miR-141 targets are associated with cancer metastasis e.g. DLC1 [29], insulin receptor substrate 2 (IRS2) [30] and salt-inducible kinase 1 (SIK1) [31]. SIK1 is particularly of interest because SIK1 is able to interact with LKB1 which in turn, enhances p53-dependent anoikis and suppresses cancer metastasis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous downregulation of PTEN and DLC1 in MCF-7 cells does not enhance cell proliferation, however, enhances cell migration [51]. DLC1 is negatively regulated by miRNAs in colorectal cancer [54,55], however, the possible DLC1 regulation by miR-26a has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%